Pre-Service Teachers' Experiences with Chatgpt During a Vocational High School Teaching Practicum - Ihsanurrahmah, Fathonah; Unsiah, Frida; Dewi, Dian Novita; Aiman, Amirul (Universitas Pendidikan Mandalika, 2025)
Incorporating ChatGPT in the educational field rapidly gained attention for its potential in the teaching and learning process, particularly in English for Specific Purposes (ESP). This exploratory case study investigates pre-service teachers’ experiences using ChatGPT during their teaching practicum in vocational high schools. Data were collected through a Focus Group Discussion (FGD) with 4 pre-service teachers from different vocational majors. The findings revealed that ChatGPT served as a valuable teaching assistant, helping pre-service teachers generate content-specific materials, plan student activities, and design assessments. Pre-service teachers also noted ChatGPT's usefulness in addressing challenges related to limited technical vocabulary resources and subject-specific content. However, this study identified several limitations in using ChatGPT, including inaccuracies in specialized terminology, rigid language outputs, and overly simplistic assessment tasks that required careful prompting and editing. This study highlights the need for strategic incorporation of AI tools in teacher education and suggests further research to optimize AI applications in vocational education settings